2000
DOI: 10.1200/jco.2000.18.4.724
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Versus Doxorubicin as First-Line Single-Agent Chemotherapy for Metastatic Breast Cancer: A European Organization for Research and Treatment of Cancer Randomized Study With Cross-Over

Abstract: At the dosages and schedules used in the present study, doxorubicin achieves better disease and symptom control than paclitaxel in first-line treatment. Doxorubicin and paclitaxel are not totally cross-resistant, which supports further investigation of these drugs in combination or in sequence, both in advanced disease and in the adjuvant setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
141
0
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(156 citation statements)
references
References 31 publications
5
141
0
10
Order By: Relevance
“…By contrast, there is no standard regimen recommended in the metastatic setting. In cases with life-threatening metastatic lesions or rapidly growing tumors, regimens that are expected to control lesions quickly, such as simultaneous administration of taxanes and anthracyclines, or taxanes in combination with either gemcitabine, capecitabine or bevacizumab, should be applied (4)(5)(6)(7)(8)(9)(20)(21)(22)(23). However, a proportion of the patients exhibit disease progression during or after receiving these cytotoxic regimens, even if favorable combinations are selected.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, there is no standard regimen recommended in the metastatic setting. In cases with life-threatening metastatic lesions or rapidly growing tumors, regimens that are expected to control lesions quickly, such as simultaneous administration of taxanes and anthracyclines, or taxanes in combination with either gemcitabine, capecitabine or bevacizumab, should be applied (4)(5)(6)(7)(8)(9)(20)(21)(22)(23). However, a proportion of the patients exhibit disease progression during or after receiving these cytotoxic regimens, even if favorable combinations are selected.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The effectiveness of paclitaxel in metastatic anthracycline-resistant breast cancer led to several large adjuvant clinical trials. The first of these to be reported, US Intergroup trial INT 0148 (CALGB 9344), demonstrated an improvement in diseasefree and overall survival from the addition of four cycles of paclitaxel to four cycles of cyclophosphamide and doxorubicin.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 21 eligible studies, of which three are ongoing (Table 2) (Dieras et al, 1995;Bishop et al, 1999;Chan et al, 1999;Nabholtz et al, 1999Nabholtz et al, , 2003Sjostrom et al, 1999;Luck et al, 2000;Paridaens et al, 2000;Bonneterre et al, 2001Bonneterre et al, , 2002Bonneterre et al, , 2003Jassem et al, 2001;Zielinski et al, 2001;Biganzoli et al, 2002;Icli et al, 2002;Talbot et al, 2002;Bontenbal et al, 2003;Sledge et al, 2003;Goldhirsch, 2005;Heidemann, 2005). An additional two studies were identified but excluded: the status of one as a randomised trial was unclear (Gebbia et al, 2003), and the second randomised women to cease vs continue paclitaxel (Gennari et al, 2001).…”
Section: Resultsmentioning
confidence: 99%